Salvia miltiorrhiza (Danshen) Injection Ameliorates Iron Overload-Induced Cardiac Damage in Mice - Zhang, Jian-ping; Zhang, Yuan-yuan; Zhang, Ying; Gao, Yong-gang; Ma, Juan-juan; Wang, Na; Wang, Jiang-yan; Xie, Yun; Zhang, Feng-hua; Chu, Li (Planta Medica, 2013)
The traditional Chinese medicinal herb Danshen (Salvia miltiorrhiza), first recorded in the “Shen Nongʼs Herbal Classic”, has long been used to treat cardiovascular conditions, although the mechanism(s) underlying its effects remain unclear. Here, an iron dextran injection (50 mg · kg−1 per day) was delivered intraperitoneally to establish a mouse model for investigating the ameliorative effects of Danshen injection (low dose at 3 g · kg−1 per day or high dose at 6 g · kg−1 per day) on iron overload-induced cardiac damage. The iron-chelating agent deferoxamine (100 mg · kg−1 per day) was administered as a positive control. The main constituents of Danshen injection, salvianic acid A (danshensu), protocatechuic aldehyde, and salvianolic acid B, were quantified at concentrations of 2.15, 0.44, and 1.01 mg · mL−1, respectively, using HPLC with UV detection. Danshen injection significantly lowered cardiac iron deposition and the concentration of the lipid oxidation product malondialdehyde, as well as improved cardiac superoxide dismutase and glutathione peroxidase levels in iron-overloaded mice. Serum levels of creatine kinase, creatine kinase isoenzyme, and lactate dehydrogenase in the iron-overloaded mice were significantly elevated (up to ~ 160 %), whereas their activities were downregulated by Danshen injection by 25 ~ 35 % at the high dose and by ~ 20 % at the low dose. Morphological changes of cardiac tissue analyzed by hematoxylin and eosin staining indicated that lesions induced by iron overload could be ameliorated by Danshen injection dose-dependently. Altogether, these results illustrated that the protective effects of Danshen injection were at least in part due to decreased iron deposition and inhibition of lipid peroxidation.
Keywords: Salvia miltiorrhiza; Lamiaceae; cardioprotection; antioxidation; HPLC-UV